2005
DOI: 10.1111/j.1600-0501.2005.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical and biological complications/failures with single crowns and fixed partial dentures on implants: a 10‐year prospective cohort study

Abstract: The three groups of suprastructures demonstrated marked differences in their patterns of failures and complications. Complications increased the risk for failure. Support by CRF, University of Berne, Switzerland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
244
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(264 citation statements)
references
References 22 publications
11
244
1
8
Order By: Relevance
“…Non-rigid connection has the potential of intrusion of teeth. [14][15][16][17] A review of the literature will reveal that there are many authors who advocate this tooth-implant connection despite this mis-match of mobility. 12,28 This connection is used to potentially gain support from the tooth, to preserve the tooth or to provide stability to rotational forces directed at the screw joint of the implant supported part of the restoration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-rigid connection has the potential of intrusion of teeth. [14][15][16][17] A review of the literature will reveal that there are many authors who advocate this tooth-implant connection despite this mis-match of mobility. 12,28 This connection is used to potentially gain support from the tooth, to preserve the tooth or to provide stability to rotational forces directed at the screw joint of the implant supported part of the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, when this type of connection occurs the phenomenon of intrusion of the tooth has been reported. [14][15][16][17]21,23 One rational method has been reported that can potentially allow sharing of load between tooth and implant and eliminate the problem of intrusion of teeth. 34 This technique has been modified and will be described in the following patient presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Het overlevingspercentage na 5 jaar van kleinere en grotere vaste bruggen op implantaten was 95,2%, en na 10 jaar 86,7%. Het laatste percentage is echter gebaseerd op slechts 3 onderzoeken Lekholm et al, 1999;Brägger et al, 2005). Het overAfb.…”
Section: Vaste Prothetische Constructiesunclassified
“…Het laatste percentage is echter gebaseerd op slechts 1 onderzoek (Brägger et al, 2005). Recentere onderzoeken waarin solitaire implantaatgedragen kronen in de esthetische zone van de bovenkaak zijn geëvalueerd, lieten vergelijkbare complicaties zien na 5 en 10 jaar (Visser et al, 2009b;Gotfredsen, 2009).…”
Section: Onderzoek En Wetenschap Meijer Ea: Complicaties Bij Patiënunclassified